Generalization of the radiative fraction correlation for hydrogen and hydrocarbon jet fires in subsonic and chocked flow regimes. (17th May 2018) - Zhou, Kuibin; Qin, Xiaole; Wang, Zhenhua; Pan, Xuhai; Jiang, Juncheng
Abstract: The radiative fraction is one key parameter to characterize the jet flame combustion dynamics and to calculate the thermal radiant heat emitted from jet fire. A theoretical analysis is conducted to clarify the key parameters that dominate the radiative fraction of jet fires, with discussion of the limitation of previous radiative fraction correlations. A completely new dimensionless group, consisting of the mass fraction of fuel at stoichiometric conditions, the density ratio of fuel gas to ambient air and the flame Froude number, is proposed to correlate the radiative fraction of jet fires. The current up-to-date experimental data are used to build the radiative fraction correlation that covers orifice exit diameters from one to hundreds of millimeter, hydrogen, methane and propane fuels, vertical and horizontal jets, buoyance- and momentum-controlled releases, subsonic, sonic and supersonic jets. It is found that the source Froude number can fit the radiative fraction of a particular fuel jet fire. However, the new dimensionless group can correlate the radiative fractions of fuel-different jet fires. The predictive capability of the new correlation exceeds that of previously published work based on the source Froude number only or the global residence time with/without correction factors. Highlights: The key parameters are derived to dominate the radiative fraction of jet fire. The effect of influence factors on the radiative fraction are physically interpreted. A generalized correlation is developed for the radiative fraction of jet fire.